THE INFLUENCE OF MOTIVATION AND COMPENSATION TOWARDS EMPLOYEES PERFORMANCE - Sri Aprianti Tarigan; Benny Lim; Susanto; Mardaus Purba; Wivenny (Institute of Computer Science (IOCS), 2021)
The success of a company is influenced by employee performance. By improving employee performance will make it easier for company goals to be achieved. One factor that can improve employee performance is the provision of compensation and motivation. This study aims to determine and analyze the influence of motivation and compensation on employee performance. From the observations of researchers in the field, PT. Surya Sumatera Indah Sejahtera seems to be less motivated in terms of the way services are provided to customers and employees also seem less enthusiastic at work. Employees who work at PT. Surya Sumatera Indah Sejahtera receives compensation that can only meet their needs, meaning that compensation is not in accordance with the prevailing general provisions (civil servant salary regulations and regional minimum wages). The purpose of this study was to determine the influence of motivation and compensation to employees’ performance. The writer collected data by questionnaire. The population in this study is all employees of the company amounted to 169 persons. The writer use Slovin Formula so that the sample is amounted to 119 persons. The conclusion from this research is motivation and compensation have a positive and significant effect on employee performance at PT. Surya Sumatera Indah Sejahtera. Partially, each variable motivation and compensation have a positive and significant effect on employee performance at PT. Surya Sumatera Indah Sejahtera.